Comparison of Laser and Oven Annealing Effects on Hydrogen and Microstructure in Thin Film Silicon. Issue 1770 (13th May 2015) - Beyer, W.; Bergmann, J.; Breuer, U.; Finger, F.; Lambertz, A.; Merdzhanova, T.; Nickel, N.H.; Pennartz, F.; Schmidt, T.; Zastrow, U.
ABSTRACT: Laser and oven annealing effects on hydrogen concentration, hydrogen diffusion and material microstructure in hydrogenated amorphous silicon films deposited on crystalline silicon substrates are compared. For laser annealing, a 6 W green (532 nm) continuous wave laser with 100 µm focus diameter was applied and samples of about 1 cm 2 were scanned in ambient with a line distance of 50 µm and at a speed of 1 – 100 mm/s. Hydrogen content and microstructure were measured by infrared spectroscopy, and hydrogen diffusion was investigated by secondary ion mass spectroscopy (SIMS) measurements of depth profiles of deuterium and hydrogen in layered structures of deuterated and hydrogenated material. The results show that in both annealing experiments hydrogen diffuses predominantly in form of atoms although some formation of H2 molecules cannot be excluded. By comparison of laser and oven treatment, an effective temperature describing the laser treated state can be defined. Furthermore, the temperature of the thin silicon film during laser treatment is estimated.